MANTRA MELAUT PADA ETNIS MANDAR LONTAR: INTERPRETASI SEMIOTIKA RIFFATERRE (FISHING MANTRAS ON THE MANDAR LONTAR ETHNICITY: RIFFATERRE'S INTERPRETATION OF SEMIOTICS) - Ardiansyah Ardiansyah (Universitas Lambung Mangkurat, 2023)
AbstractFishing Mantras on the Mandar Lontar Ethnicity: Riffaterre's Interpretation of Semiotics. The research objectives were to describe (1) the function of the mantras contained in the Mandar Lontar Ethnic fishing mantras; (2) the indirect expression of the Mandar Lontar Ethnic fishing mantras; and (3) the meaning of the Mandar Lontar Ethnic fishing mantras based on heuristic and hermeneutic readings. The method used in this research was descriptive research method with a qualitative approach, while the type of research was oral literature research with Riffaterre's semiotic theory. The results of this study were the function of the Mandar Lontar ethnic fishing mantras in general as a tool or medium to convey a request or prayer to Allah Swt. The indirect expression contained in the sandeq, wind, sailing, fishing, and bagang mantras in the Mandar Lontar ethnicity were the replacement of meaning and deviation of meaning and the creation of meaning. In the heuristic reading of the Mandar Lontar ethnic fishing mantras, various spell texts were found did not have a literal meaning. There were also texts of the Mandar Lontar ethnic fishing mantras which had different meaning if it were described in words and sentences, while in hermeneutic reading, it was found that there were meaning behind the metaphor that was characteristic of Islam.Keywords: mantras, fishing, mandar lontar ethnicity, interpretation, riffaterre semioticsAbstrakMantra Melaut pada Etnis Mandar Lontar: Interpretasi Semiotika Riffaterre. Tujuan penelitian adalah untuk mendeskripsikan (1) fungsi mantra yang terdapat dalam mantra melaut Etnis Mandar Lontar; (2) ketidaklangsungan ekspresi pada mantra melaut Etnis Mandar Lontar; dan (3) makna mantra melaut Etnis Mandar Lontar berdasarkan pembacaan heuristik dan hermeneutik. Metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif dengan pendekatan kualitatif, sedangkan jenis penelitiannya adalah penelitian sastra lisan dengan teori semiotika Riffaterre. Hasil penelitian ini adalah fungsi mantra melaut etnis Mandar Lontar secara umum merupakan sebagai alat atau media untuk menyampaikan permohonan atau doa kepada Allah Swt. Ketidaklangsungan ekspresi yang terdapat dalam mantra sandeq, angin, berlayar, memancing, dan bagang pada etnis Mandar Lontar yaitu penggantian arti dan penyimpangan arti serta penciptaan arti. Dalam pembacaan heuristik pada mantra melaut etnis Mandar Lontar ditemukan berbagai teks mantra yang tidak mempunyai arti harfiah. Ada juga teks mantra melaut etnis Mandar Lontar yang mempunyai arti yang berbeda jika diuraikan perkata dan perkalimat, sedangkan dalam pembacaan hermeneutik menemukan adanya makna dibalik metafora yang berciri khas Islam.Kata-kata kunci: mantra, melaut, etnis mandar lontar, interpretasi, semiotika riffaterre